Management of Second Trimester Fetal Demise in a Noncommunicating Uterine Horn - R. Tyler Hillman; Homer G. Chin; Sheila K. Mody (Hindawi Limited, 2015)
Müllerian anomalies are uncommon but when present they can increase the risk of obstetrical complications. Anomalies such as bicornuate and unicornuate uterus can also increase the surgical risks of pregnancy termination. The diagnostic approach and surgical management must be individualized for each patient so that the termination procedure is safe and preserves fertility. We present a case of a patient with a 17-week pregnancy with fetal demise in a noncommunicating right uterine horn. Laparotomy and hysterotomy were required for evacuation of the fetus. The use of appropriate imaging studies to diagnose suspected uterine anomalies and a flexible and individualized operative strategy are essential for reducing complications associated with the termination of abnormal or unintended pregnancies in women with Müllerian anomalies.